Peripheral blood mononuclear cell mitochondrial copy number and adenosine triphosphate inhibition test in NAFLD - Lee, A-Hyeon; Oh, Ju Hee; Kim, Hyun Sung; Shin, Jeong-Hun; Yoon, Eileen L.; Jun, Dae Won (Frontiers in Endocrinology, 2022)
Background & Aim: Nonalcoholic fatty liver disease (NAFLD) is associated with mitochondrial dysfunction. This study aims to develop biomarkers for assessing mitochondrial dysfunction in patients with NAFLD. Methods: Mitochondrion-associated transcriptome analysis was performed. Peripheral blood mononuclear cells obtained from patients with NAFLD (69) and healthy controls (19) were used to determine the mitochondrial DNA (mtDNA) copy number. A mitochondrial inhibition substrate test (ATP assay) was performed in HepG2 cells using the patient serum. Results: Hepatic mRNA transcriptome analysis showed that the gene expression related to mitochondrial functions (mitochondrial fusion, apoptotic signal, and mitochondrial envelope) increased in patients with steatohepatitis, but not in those with NAFL. Gene set enrichment analysis revealed that the upregulated expression of genes is related to the pathways of tricarboxylic (TCA) cycle and Deoxyribonucleic acid (DNA) replication in patients with steatohepatitis, but not in healthy controls. The mtDNA copy number in the peripheral blood mononuclear cells was 1.28-fold lower in patients with the NAFLD than that in healthy controls (P < .0001). The mitochondrial inhibition substrate test showed that the cellular adenosine triphosphate (ATP) concentration was 1.2-fold times less in NAFLD patients than that in healthy controls (P < .0001). The mtDNA copy number and mitochondrial ATP inhibition substrate test demonstrated negative correlations with the degree of hepatic steatosis, whereas the ATP concentration showed a positive correlation with the mtDNA copy number. Conclusion: The mitochondrial copy number of peripheral blood mononuclear cells and mitochondrial ATP inhibition substrate can be used as biomarkers for assessing the mitochondrial dysfunction in patients with NAFLD.